Kajian Jarak Aman Antara Arrival Traffic Dan Departure Traffic Pada Unit Aerodrome Control Tower di Perum LPPNPI Kantor Cabang Pontianak - Zinat Tamami; Endang Sugih Arti; Pangsa Rizkina Aswia (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
Supadio International Airport is an airport that serves various types of aircraft (Boeing, Airbus, ATR, Hawk, CN259), and does not have a rapid exit taxiway, in its guidance, Perum LPPNPI Pontianak Branch Office enforces rules for Boeing and Airbus-type arrival traffic for backtrack at the end of the runway, but this rule does not apply to aircraft with other types such as ATR and Cessna. This of course creates a time difference to clear the runway for arrival traffic of the Airbus and Boeing types. This study aims to obtain a safe distance between arrival traffic and departure traffic at the Perum LPPNPI Pontianak Branch Office by applying the calculation of The Brazilian Air Navigation Management Center (CGNA) Runway Capacity Calculation by adjusting the current airport conditions. From the research results, it is found that the value of the safe distance between arrival traffic and departure traffic by considering the aircraft classification can produce a more optimal safe distance.